A atual reforma do ensino médio no SESI/SENAI do espírito santo: configuração curricular dos itinerários formativos e BNCC - Silva, Marcos Lengrub da (2021)
This paper aims at analyzing the reform of high school in Espírito Santo implemented in the Industry social service (SESI) and the National Service of Social Learning (Senai) through the combined offer of the Technical-Professional Itinerary and the Common National Curriculum Base (BNCC), in the legal framework defined by Law No. 13.415/2017 and by other norms (National High school Curriculum Guidelines - Dcnem; National Curriculum Guidelines for Professional and Technological Education - Dcnept; other resolutions, decrees and ordinances). These institutions in the S system, focused on professional training, have been seeking, through their units in the states of Alagoas, Bahia, Ceará, Espírito Santo and Goiás to take the lead in the current reform by demonstrating its validity and feasibility. Thus, at the local level, along with the offer of other modalities such as technical courses, Initial and Continuing Training - FIC; Basic Education articulated with Professional Education - Ebep; and others) Senai-ES starts to incorporate to its portfolio the offer of BNCC Itinerary V - Technical and Professional Training, whereas Sesi-ES has become responsible for both BNCC offer and other itineraries by enhancing the performance of its educational structures in this teaching model. In this study, we address the “New High School” Project connected with the reform of high school in its curricular configuration developed through the experience of Henrique Meyerfreund Basic and Professional Education Center, which is a teaching unit at Sesi/Senai-ES located in Serra city/ES. The curriculum, which is consisted of the knowledge acquired in the BNCC (with 1,800 hours) and the knowledge and actions of professional training (with 1,200 hours), has represented a significant reduction in the workload and content when compared to the integrated model of technical professional education of middle level intertwined with high school (EPTNM and EM in a single enrollment), and with the articulated model of high school technical professional education juxtaposed with high school (EPTNM and EM in two enrollments. But this is not only a reduction in quantities but also a reduction in qualities, with the prioritization of certain knowledge in relation to the others and with its articulation to a fragmented, pragmatic and individualistic teaching conception, whose horizon is not an omnilateral, integral training in a polytechnic curriculum. In this model, a monotechnical curriculum is asserted with an emphasis in Portuguese and mathematics. This new proposition, inserted in this field of dispute, which became high school, has represented a defeat to formation in the process of maturation by causing omnilateral education, which was in the last decades an educational setback of maturation that may cause great harm to Brazilian education and, why not to the immense youth who must, in the coming years, attend a fragmented, adaptive and flexible high school, characteristics that are favorable to the maintenance of the regime imposed by capital in our country. However, this curriculum, expected to operate in this rationality, in practice, when put into action, it opens many possibilities to overcome the limits imposed by the model. Besides, the effort undertaken by educators in these institutions, in finding infrastructure and motivated students, full of expectations and dreams, they can make the new high school something that points to a limited but resistant humanization, situated in the field of experience, always valuable in educational processes.